Conservation agriculture in East and Southern Africa main messages - Rosenstock, Todd S.; Lamanna, Christine; Thierfelder, Christian L. (2016)
What is and what is not climate-smart agriculture (CSA)? That existential question sparks debate, complicates implementation and fractures the development community. Many institutions are developing 4-10 page ‘technical briefs’ describing the ‘climate-smartness’ of interventions (ie, the impact of interventions on indicators of productivity, resilience and mitigation) to answer this question. Oftentimes, technical briefs, however, are data-lite increasing potential for biased assessments. CSA X-Rays were designed to provide a counter point to this: to be pithy and detailed analysis of what science and scientists tell us about the ‘climate-smartness’ of CSA interventions or CSA in a specific location. In short, this pilot project intended to innovate on the ‘CSA technical brief’. This CSA-Xray examine the climate-smartness of conservation agriculture.